1H NMR-based metabonomics of the hypoglycemic effect of polysaccharides from Cordyceps militaris on streptozotocin-induced diabetes in mice. Issue 10 (18th May 2020) - Shang, Xiao-Lan; Pan, Li-Chao; Tang, Yun; Luo, You; Zhu, Zhen-Yuan; Sun, Hui-Qing; Meng, Meng; Zhang, Yong-min
Abstract: The crude polysaccharide was extracted from Cordyceps militaris . Material ratio of powder and water was 1:10. The polysaccharide was successively purified by Sevag and chromatography on Sephadex G-100 column to produce a polysaccharide fraction termed CBPS-II. The average molecular weight of CBPS-II was 1.273 × 10 3 kDa. The study was conducted to investigate the hypoglycemic effect of Cordyceps militaris polysaccharide on diabetic mice. Analysis of the clinical chemistry of the serum samples included serum creatinine (CRE), urea nitrogen (BUN), triglyceride (TG) and total cholesterol (TC). Results revealed that a certain dose of polysaccharide can alleviate the symptoms of metabolic disorders of diabetes, contributing to the body to restore the normal levels. The metabolic profiling method was adopted to find the related biomarkers and the metabolic pathway of diabetes. Moreover, results showed that 100 mg·kg −1 of Cordyceps polysaccharides can effectively reduce the blood glucose level of diabetic mice, thus regulating the metabolism of their energy, amino acids and intestinal microbes. The biomarkers noted in their metabolism were glucose, lactic acid, 3-hydroxy butyric acid, creatine, glutamate, valine, leucine, isoleucine and very low density lipoprotein (VLDL). Graphical Abstract: